2019
DOI: 10.1093/jxb/erz306
|View full text |Cite
|
Sign up to set email alerts
|

The fungal sesquiterpenoid pyrenophoric acid B uses the plant ABA biosynthetic pathway to inhibit seed germination

Abstract: Pyrenophoric acid (P-Acid), P-Acid B, and P-Acid C are three phytotoxic sesquiterpenoids produced by the ascomycete seed pathogen Pyrenophora semeniperda, a fungus proposed as a mycoherbicide for biocontrol of cheatgrass, an extremely invasive weed. When tested in cheatgrass bioassays, these metabolites were able to delay seed germination, with P-Acid B being the most active compound. Here, we have investigated the cross-kingdom activity of P-Acid B and its mode of action, and found that it activates the absci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Three metabolites showed phytotoxic activity by reducing coleoptile elongation of cheatgrass seedlings [ 209 , 210 ]. Among three metabolites, pyrenophoric acid B ( 314 ) was the most phytotoxic to use the abscisic acid (ABA) biosynthesis pathway at the level of alcohol dehydrogenase ABA2 to reduce seed germination of cheatgrass [ 211 ].…”
Section: Terpenoidsmentioning
confidence: 99%
“…Three metabolites showed phytotoxic activity by reducing coleoptile elongation of cheatgrass seedlings [ 209 , 210 ]. Among three metabolites, pyrenophoric acid B ( 314 ) was the most phytotoxic to use the abscisic acid (ABA) biosynthesis pathway at the level of alcohol dehydrogenase ABA2 to reduce seed germination of cheatgrass [ 211 ].…”
Section: Terpenoidsmentioning
confidence: 99%
“…They are isolated from fungi (ascaulitoxin, pinolidoxin, putaminoxin, spirostaphylotrichins, macrocidins, and others, and more recently, pyrenophoric acids, colletochlorins E and F, cochliotoxin, and phaeosphaeride A ) and by allelopathic plants as inuloxins A–D and α-costic acid obtained from Dittrichia viscosa (syn. Inula viscosa ). , For some potential herbicidal metabolites, the absolute configuration was assigned as an important feature that has an impact on the biological activity. Furthermore, some studies were carried out to further characterize their biological activity, , the structure–activity relationships, , the mode of action, and their total enantioselective synthesis. , …”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that it uses the ABA biosynthesis pathway at the level of alcohol dehydrogenase ABA2 to achieve this inhibition. This result suggested that P. semeniperda may manipulate plant ABA biosynthesis in the seed as a strategy to reduce germination, increasing its ability to cause seed mortality and thereby increase its fitness through higher reproductive success [92].…”
Section: Phytotoxins Produced By Pyrenophora Semeniperdamentioning
confidence: 99%
“…Pyrenophoric acid B (30, Figure 3) P. semeniperda Phytotoxic to Arabidopsis thaliana and B. tectorum [91,92] Pyrenophoric acid C (31, Figure 3 Triticone D (15, Figure 2)…”
Section: P Tritici-repentismentioning
confidence: 99%